Study of the Cytotoxic Effect of New Copper(II) Complexes and Aqueous Extract of Origanum Vulgare L. Plant on Cancer )Cell Line RD) - Dhahir, Saadiyah A; Murtadha, Jinan H; Abdul Razzaq, Iman H (Al-Nahrain Journal of Science, 2012)
The new complexes of copper (II) 1,2 where L1 in complex (1) was 2-Amino-5-[2-amino -5-(3,4,5-trimethoxy-benzyl)-pyrimidinyl-4-azo]-phenol, while L2 was 2-[2-Amino-5-(3,4,5-trimethoxy-benzyl)-pyrimidinyl-4-azo]-4-bromophenol and aqueous extract of Origanum Vulgare L.plant (after the chemical assay)were studied on the growth on of Rhabdomyo sarcomas(RD)cell line in human by using in vitro system and compared with anticancer drug cisplatin (cis-pt) as a posative control.The cancer cells were treated with different concentration (31.25, 62.5, 125, 250)μg/ml for each of the three treatments and cis-pt after 72 hour exposure time. The cytotoxic activity was tested by inhibition rate as parameter. The results showed significant differences (p<0.05) for each three treatments when the inhibition rates were increased. The inhibition levels was reached to 48.13% , 51.75% and 51.63% respectively at 250μg/ml.There was strong correlation between the three treatments and the different concentrations in comparison with cisplatin.